(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the free throw movements of basketball players from the Faculty of Sport Science and Health, Universitas Negeri Makassar (FIKK UNM) using a biomechanical approach. The research employed a quantitative descriptive method, with data collected through observation, high-speed video recording, and analysis using biomechanical software such as Kinovea. The study population included all players of the FIKK UNM basketball team, with a sample of 50 players selected using purposive sampling. The results indicate that the free throw movement patterns generally follow ideal biomechanical principles, encompassing the preparation, execution, and follow-through phases. However, several technical deficiencies were identified, including body imbalance during the preparation phase, premature ball release, suboptimal knee angles, and inconsistent follow-through, all of which affected shot accuracy. The primary factors influencing free throw success include body balance, coordination of body segments, and psychological control. This study emphasizes the importance of biomechanics-based training, including video analysis for objective evaluation of movements, corrective exercises to address technical errors, development of coordination and balance, and enhancement of focus and psychological control. The implementation of this approach is expected to improve the consistency and accuracy of free throws and enhance their contribution to overall team performance.